Xpider: Design and Development of a Low Cost VTOL UAV Platform. (3rd January 2013) - Rincon, Oscar Higuera; Durán, Carlos E. Agüero
The main aim of the Xpider project is to analyse, design and develop a low-cost VTOL (Vertical Take Off and Landing) UAV (unmanned aerial vehicle) platform in order to provide a common architectural model for both embedded software and GCS (Ground Control Station) software and communications system. This architectural model should be adaptable to any other hardware platforms or sensors. Some of the key points of the project were, on the one hand, the stabilization process using low-cost sensors and all the associated issues with low quality instruments, on the other hand the interface between the stabilization controller and the navigation controller, not forgetting the secure communication protocols. Additionally, as a side effect of the stabilization process analysis, a new metaheuristic optimization search algorithm has been developed to be used in PID (Proportional Integral Derivative) controllercalibration tuning and has been successfully applied in the stabilization controller.